Serum salusins levels are increased and correlated positively with cyst size in ovarian endometrioma - Sahin, Levent; Bozkurt, Murat; Celik, Onder; Celik, Nilufer; Aydin, Suleyman; Gencdal, Servet (Taylor & Francis Ltd, 2015)
Objectives: The objective of this study is to evaluate plasma concentrations of salusin-alpha and salusin-beta levels in women with endometrioma and non-endometriotic benign ovarian cysts. Method: Endometrioma patients (n = 14), non-endometriotic ovarian cysts (n = 14), and age-matched normal healthy fertile subjects (n = 14) participated in this study. Plasma salusin-alpha and salusin-beta levels at the time of mid-luteal phase before and 3 months after L/S cystectomy were measured using ELISA and EIA tests, and their relation with demographic parameters was also assessed. Results: The mean salusin-alpha and salusin-beta levels were significantly higher in women with endometrioma before the removal of cyst compared with cases with non-endometriotic cyst and fertile cases. Surgical removal of the endometrioma decreased the mean salusin-alpha and salusin-beta levels to the level of those with non-endometriotic cyst before and after the cystectomy and fertile women, in both unilateral and bilateral endometrioma cases. Plasma salusin-beta concentrations were found to be positively correlated with age, size of cyst, bilaterality, and salusin-alpha levels. Salusin-beta values showed no correlations to BMI and size of the ovarian cysts. Conclusions: Plasma salusin-alpha and salusin-beta levels are increased in endometrioma patients and positively correlated with endometrioma size. Laparoscopic removal of the endometrioma by stripping technique decreases the salusin levels to a similar level of fertile women.
Keywords: Angiogenesis; endometriosis; infertility; ovary; salusins